Assessment of coagulation profile by thromboelastometry in adult patients with cyanotic congenital heart disease. (1st January 2016) - Rupa-Matysek, Joanna; Trojnarska, Olga; Gil, Lidia; Szczepaniak-Chicheł, Ludwina; Wojtasińska, Ewelina; Tykarski, Andrzej; Grajek, Stefan; Komarnicki, Mieczysław
Abstract: Background: Patients with cyanotic congenital heart disease (CCHD) have an increased risk of bleeding and thrombotic complications. Prolonged conventional coagulation screening parameters, such as activated partial thromboplastin time or prothrombin time, are reported in less than 20% of CCHD patients. Methods: The aim of this study was to determine the haemostatic abnormalities in 32 adult patients with CCHD by rotation thromboelastometry (ROTEM) with assessment of coagulation dynamic properties, as a guide for perioperative prophylaxis or haemostatic therapy. The control group consisted of 35 healthy subjects. Results: Our results suggest that CCHD patients, in comparison to healthy controls, had a tendency to hypocoagulate with delayed activation of haemostasis and clot formation, initiated by both intrinsic and extrinsic activators. The growth of the clot was slower and the clot firmness was decreased, which may additionally contribute to bleeding diathesis. Moreover, the clot lysis readings suggest higher clot stability in the CCHD group. All velocity parameters were markedly lower in the CCHD patients, indicating a decreased rate of clot formation. Although coagulation tests and platelet count were normal, the usefulness of rotation thromboelastometry in monitoring or guiding therapy in CCHD patients is demonstrated. Conclusion: In conclusion, our results provide new insights into the data on hypocoagulation with impaired clot lysis in adult CCHD patients as determined by ROTEM. Our findings may assist in determining the optimal management of patients with CCHD undergoing surgery.